Kajian Kinerja Pemerintah Kelurahan dalam Mewujudkan Program Permukiman Green-Village di Kelurahan Gayamsari, Kota Semarang - Puspita, Astrini Ayu (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2014)
A settlement which is trying to promote ecological aspects are Gayamsari village, Semarang. The local government initiated a Gayamsari Green-village program, to prioritizing environmental friendly development. However, there are many problems that hamper the realization of green-village, there are lack of green space, flooding caused by inadequate drainage, and Gayamsari community’s effort in realizing green-village is low. It shows that the performance of the village’s government in green-village has not been optimally realized, because of many environment problems and the village’s government has not been good enough to motivate Gayamsari’s community in realizing green-village. The aim of this study is to assess the performance made by village’s government of Gayamsari village in realizing green-village program. The results of this study shows that the performance of village’s government in realizing green-village is good enoughThe positive factors of performance are good governance from village’s government and good cooperation with community. Factors that cause the bad performance are, lack of implementation of green-village indicator and lack of monitoring activity from the village’s government, so that the existing environmental activities are not sustainable.